The Effectiveness of the Talaqqi Method in Enhancing Arabic Reading Proficiency at Pondok Pesantren Wirdullatifah Nahdlatul Wathan Banjar Manis - Dwi Istati Apriana; Muhamad Hasyim; Aulia Sa’ida; Isro’ Sriwati; Ahmad Fatir Ibnullah5; Hilman Maulana; Ifradin; Arif Usman (Indonesian Journal of Education and Science, 2026)
This study addresses the need for effective instructional methods to improve Arabic reading proficiency in pesantren, particularly through direct teacher–student interaction. The study aims to examine the effect of the Talaqqi method on students’ Arabic reading proficiency and determine the magnitude of its contribution. A quantitative quasi-experimental design was employed with 40 students at Pondok Pesantren Wirdullatifah Nahdlatul Wathan Banjar Manis selected through purposive sampling. Data were collected using Arabic reading proficiency tests administered before and after the intervention and analyzed using descriptive statistics, the Kolmogorov–Smirnov normality test, paired-samples t-test, linear regression, and Cohen’s d. The findings reveal that the mean reading proficiency score increased from 56.32 before the intervention to 75.45 after the intervention. The paired-samples t-test showed a statistically significant improvement (t = 10.67, df = 39, p = 0.0001). Regression analysis indicated a positive coefficient (B = 0.44) and an R² of 0.62, indicating that 62% of the variance in Arabic reading proficiency was explained by the Talaqqi method within the model. The effect size was large (Cohen’s d = 1.50). The study concludes that Talaqqi is an effective approach for enhancing Arabic reading proficiency through modelling, direct feedback, repetition, and guided practice. The findings contribute to Arabic pedagogy and provide practical implications for pesantren-based instruction.